2023
DOI: 10.30762/sittah.v4i2.1950
|View full text |Cite
|
Sign up to set email alerts
|

Students' Responses of Joyful Learning Class in Islamic Elementary School: Flashcard Games and Visual Worksheet

Renita Donasari,
Tutik Dinur Rofiah,
Athi’illah Qurroti

Abstract: The four characteristics of young learners, which can be embodied in learning that is active, fun, concrete, and uses sensory experiences, should be considered to optimize vocabulary learning. Therefore, this qualitative research aims to investigate students' responses to the joyful vocabulary class by implementing flashcard games and visual worksheets. The instruments used were a Likert scale questionnaire, interviews, observation, and documentation, with 20 students in the second grade of SD Sunan Ampel Kedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Research by Ashfaq et al (2017) was implementing the joyful learning model in elementary school students to increase learning motivation. Research by Donasari et al (2023) was using the Likert scale questionnaire method on 20 students showed positive student responses to the joyful learning model. Last, research by Syawaluddin et al (2020) about the development of snakes and ladders game-based media to improve learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Ashfaq et al (2017) was implementing the joyful learning model in elementary school students to increase learning motivation. Research by Donasari et al (2023) was using the Likert scale questionnaire method on 20 students showed positive student responses to the joyful learning model. Last, research by Syawaluddin et al (2020) about the development of snakes and ladders game-based media to improve learning outcomes.…”
Section: Introductionmentioning
confidence: 99%